Filiazione e genitorialità fra pratiche, rappresentazioni e diritto: il caso dell’omogenitorialità in Italia - Parisi, Rosa (EtnoAntropologia, 2018)
The parent-child relationship is a dynamic, socially and legally constructed relationship. The relationship between filiation and parenting calls in play the ties between social construction and ideology of kinship and its normative determination. Through the analysis of two sentences on lesbian and gay parenting, we analyze the way in which the request for the legal recognition of homoparenting produces a circulation of cultural, symbolic and scientific references between society and the courts. These judgments call in play the legal relationships and the actions of the subjects capable of producing new legal regulations and new representations of family, parenting and filiation ties.